Internal electric field-assisted copper ions chelated polydopamine/titanium dioxide nano-thin film heterojunctions activate peroxymonosulfate under visible light to catalyze degradation of gatifloxacin: Theoretical calculations and biotoxicity analysis - Ding, Chunsheng; Lu, Yuqing; Xiang, Ming; Wu, Fen; Chen, Peng; Gan, Wei; Guo, Jun; Li, Jianrou; Ling, Qi; Zhao, Ziwei; Chen, Lei; Zhang, Miao; et al. (Journal of colloid and interface science, 2023)
[Display omitted] •Thin film photocatalysts are more recyclable and potential than powder photocatalysts in practical environments.•The degradation pathways of gatifloxacin were analyzed by combining DFT theoretical calculations and LC-MS techniques.•Polydopamine is capable of greatly limiting the leaching rate of Cu2+.•In situ XPS and DFT theoretical calculations illustrate Step-scheme charge transfer pathways. The combination of photocatalysis and peroxymonosulfate (PMS) activation is considered effective in treating organic pollutants in water; however, the photocatalysts currently used to activate PMS are primarily in powder form, which cause secondary contamination because they are difficult to recycle. In this study, copper-ion-chelated polydopamine/titanium dioxide (Cu-PDA/TiO2) nanofilm were prepared for PMS activation on fluorine-doped tin oxide substrates using hydrothermal and in-situ self-polymerization methods. The results showed that Cu-PDA/TiO2 + PMS + Vis degraded 94.8% of gatifloxacin (GAT) within 60 min, and the reaction rate constant reached 4.928 × 10-2 min−1, which was 6.25 and 4.04 folds higher than that of TiO2 + PMS + Vis (0.789 × 10-2 min−1) and PDA/TiO2 + PMS + Vis (1.219 × 10-2 min−1), respectively. The Cu-PDA/TiO2 nanofilm is easily recyclable and activates PMS to degrade GAT with no inferior performance, unlike the powder-based photocatalysts, and simultaneously maintains outstanding stability, which is highly suitable for applications in real aqueous environments. Biotoxicity experiments were conducted using E. coli, S. aureus, and mung bean sprouts as experimental subjects, and the results showed that the Cu-PDA/TiO2 + PMS + Vis system had excellent detoxification ability. In addition, a detailed investigation of the formation mechanism of step-scheme (S-scheme) Cu-PDA/TiO2 nanofilm heterojunctions was conducted by density functional theory (DFT) calculations and in-situ X-ray photoelectron spectroscopy (XPS). Finally, a specific process for activating PMS to degrade GAT was proposed, which provides a novel photocatalysts for practical applications in aqueous pollution.